Métodos de enseñanza de la historia orientados a la formación de competencias en alumnos universitarios en la región tumbes, 2012 - Corcuera Chávez, Malu Teresa (2014)
The purpose of the research was to propose a Methods of Teaching History oriented Competency Training university students in the Tumbes Region, 2012, based on problems, studies and cooperative learning, comprising the steps of design, home, process, output, feedback and evaluation. To do this, previously developed and applied to a sample comprised of 60 students from the Universidad Alas Peruvian and 60 students of the National University of Tumbes. Application of Integrated Strategies in history teaching was developed taking into account theoretical approaches and mentioned paradigms that was implemented with a total of eight sessions and developed with 30 students of the University "Peruvian Wings" and 30 students of the National University Tumbes, which constituted the experimental group and 30 students of the Universidad Alas Peruvian and 30 students of the National University of Tumbes in the control group, who were administered a test of cognitive, procedural and attitudinal competencies validated by Spearman rank method Browmm and quasi-experimental design was used to test the hypothesis and is used the "t" test with 58 degrees of freedom and a significance level of p = 0.05 . The results in Peruvian Wings University and the National University of Tumbes indicate that the average score of the experimental group applied the pre test was low, but after applied the Integrated Strategy, significant differences were observed in the three dimensions of skills (cognitive, procedural and attitudinal), since the average score increased , which allowed us to accept the formulated hypothesis (Hi) and reject the null hypothesis (Ho) and conclusion is shown that the implementation of the Integrated method of teaching strategy History significantly improve the dimensions of cognitive procedural and attitudinal competencies.